Introductory note - Fernandes, Isabel, 1953 (2011)
Introduction to Anglo-Saxónica, II:27, an issue especially devoted to Irish Literature and Culture (springing from the Irish Literature Festival, in Nov. 2007) and dedicated to the belated scholar Paulo Eduardo Carvalho